Peran Modal Psikologis dan Organizational Virtuousness terhadap Work Engagement Karyawan Generasi Milenial - Fatiya Halum Husna; Sumaryono - (Jurnal Ilmu Perilaku, 2020)
Work engagement is one of job performance predictor, but millennial is known to have lower work engagement than older generation. Psychological capital and organizational virtuousness are some important factor to increase work engagement. The aim of this study was to determine psychological capital and organizational virtuousness as work engagement predictor. This research used quantitative approach. Questionnaires used to collect data about psychological capital, organizational virtuousness, and work engagement. Analyzed by multiple linier regression with 212 millennial worker who born between 1980 until 2000 as participant. The result of hypothesis test showed in the value of F=124,809 (p<0,05), the hypothesis was accepted which explained that psychological capital and organizational virtuousness have a role as predictor of work engagement of millennial generation worker with contribution as much as 54,4%. These result provide support about improvement of work engagement through organizational virtuousness and psychological capital by optimizing leader role to giving coaching to the worker.